2021
DOI: 10.3390/en14217114
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Binder-Free and Hydrothermal Growth of Nanostructured NiCo2S4/Ni Electrodes for Solid-State Hybrid Supercapacitors

Abstract: Herein, we report a comparison of the electrochemical performance of two kinds of NiCo2S4-based electrodes for solid-state hybrid supercapacitors (HSCs). For the binder-free electrode, NiCo2S4 was grown on Ni foam by the chemical bath deposition (CBD) method. For the binder-using electrode, NiCo2S4 powder was synthesized by the hydrothermal method. FESEM images depicted the hierarchical nanostructure of NiCo2S4 synthesized by the hydrothermal method and uniform distribution of nanostructured NiCo2S4 grown on N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…The results are shown in Figure 6 . Three peaks at 190, 516, and 653 cm −1 were observed for NCS and NCS@G hybrids, whereas the peaks at 516 and 653 cm −1 belong to the F2g and A1g modes of NiCo 2 S 4 , respectively [ 7 ]. These results confirmed the formation of NiCo 2 S 4 again through the hydrothermal syntheses of NCS, NCS@G (000), and NCS@G (111).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are shown in Figure 6 . Three peaks at 190, 516, and 653 cm −1 were observed for NCS and NCS@G hybrids, whereas the peaks at 516 and 653 cm −1 belong to the F2g and A1g modes of NiCo 2 S 4 , respectively [ 7 ]. These results confirmed the formation of NiCo 2 S 4 again through the hydrothermal syntheses of NCS, NCS@G (000), and NCS@G (111).…”
Section: Resultsmentioning
confidence: 99%
“…The supercapattery has a positive electrode made up of battery-type materials to provide energy density, and the negative electrode consists of carbon-based materials to give high power density. Recently, ternary Ni-Co sulfides with rich redox-active sites and variable valence states, such as Ni 2+ /Ni 3+ , Co 2+ /Co 3+ , and Co 3+ /Co 4+ , during the charging and discharging process have been suggested as promising battery-type materials for supercapatteries; however, the low conductivity, easy agglomeration, and poor electrochemical stability of ternary Ni-Co sulfides present a series of problems to be tackled [ 6 , 7 ]. Many results have reported that the combination of high conductivity materials, such as reduced graphene oxide (rGO) or graphene (G) and Ni-Co sulfides using a hydrothermal process, can achieve a synergistic effect, leading to enhanced electrochemical performance [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The textural properties of the samples agreed with the morphology results. The surface area of the Mn-doped NiCo 2 O 4 samples with ultrasonic-assisted treatment was higher than that of the A(u) to F(u)) samples, largely because ultrasonic treatment provided an effective method to improve ion deposition compatibility through the leveling effect [22]. Costa et al [28] reported that the particle deagglomeration in the electrodeposition process combined with the ultrasound technique could be promoted due to microturbulence, microjets, shock waves, and van der Waals forces causing physical and chemical property changes.…”
Section: Porosity and Surface Area Characterizationmentioning
confidence: 96%
“…Research on preparing binder-free composite electrodes using nickel as the base material has aroused great interest in recent years [7,[20][21][22][23]. Binder-free electrodes enhance the contact between the active electrode material and the current collector, significantly reducing the risk of catalyst shedding during cycling and improving cycle stability [7].…”
Section: Introductionmentioning
confidence: 99%